Exurban and suburban forests have superior healthcare benefits beyond downtown forests - Zhu, Shuxin; He, Shuangyu; Hu, Feifei; Guo, Yundan; Su, Yan; Cui, Guofa; Li, Jiyue; Qiu, Quan; He, Qian (Frontiers in Ecology and Evolution, 2023)
To comprehensively evaluate the healthcare benefits of urban forest in different geographical spaces. We selected exurban forest, suburban forest, downtown forest, and urban control in Guangzhou, China to analyze the change characteristics of negative air ion concentration (NAIC), air oxygen content (AOC), human comfort index (HCI). Based on Criteria Importance Through Intercriteria Correlation (CRITIC) method, the urban forest comprehensive healthcare index (UFCHI) was established. Finally, the evaluation criteria for UFCHI were identified by cluster analysis. The results demonstrated that (1) The NAIC in exurban forest (2 713±1 573 ions/cm3) and suburban forest (2 147±923 ions/cm3) was evidently better than downtown forest (1 130±255 ions/cm3) and urban control (531±162 ions/cm3). (2) The AOC was in the order of exurban forest (21.17±0.38 %) > suburban forest (21.13±0.30 %) > downtown forest (21.10±0.16 %) > urban control (20.98±0.12 %). (3) The HCI in urban control (5.56±2.32) and downtown forest (5.15±1.80) is higher than suburban forest (4.02±1.53) and exurban forest (3.71±1.48). (4) The UFCHI in exurban forest (1.000), suburban forest (0.790), and downtown forest (0.378) were beneficial to human health to some extent, while urban control (0.000) was at Level Ⅳ, having no healthcare benefit. Except in winter, the UFCHI in exurban forest and suburban forest were all at Level Ⅱ and above; while downtown forest and urban control were all at Level Ⅲ and below at all seasons. Overall, urban forests in the exurbs and suburbs have better healthcare benefits than those in the downtowns. Furthermore, it is recommended that urban residents visit exurban and suburban forests for forest therapy in spring, summer, and autumn.